The Role of Digital Islamic Communication of Early Childhood Education Teachers in Internalizing Moral Values of Early Childhood Education in Tunas Bangsa Early Childhood Education and Syuhada' Haji Kindergarten in Blitar City - Choirul Hidayah (Journal of Communication Studies, 2025)
The development of digital technology and social media presents both challenges and opportunities for Early Childhood Islamic Education (PIAUD) institutions in internalizing moral values in young children. Teachers are no longer solely educators but also communicators capable of utilizing digital media to effectively convey Islamic values. This study aims to describe the role of digital Islamic communication conducted by PIAUD teachers in the internalization of moral values among young children at PAUD Tunas Bangsa and TAB Syuhada’ Haji in Blitar City.A descriptive qualitative approach was employed with 10 PIAUD teachers who actively use social media as a learning medium as the research subjects. Data were collected through in-depth interviews, classroom observations, and documentation of digital learning activities, then analyzed using Miles and Huberman’s interactive model through the stages of data reduction, data display, and conclusion drawing.The findings show that teachers utilize platforms such as WhatsApp, Instagram, and YouTube to deliver Islamic learning materials, daily prayers, Islamic stories, and moral habituation for children. Interactive digital learning materials containing images, animations, and Islamic narratives were found to be effective in increasing children’s and parents’ engagement, as they align with the visual and interactive characteristics of early childhood. The successful internalization of moral values was also supported by parental involvement, digital literacy training for teachers, and the management of a safe digital environment.This study concludes that digital Islamic communication functions not only as a medium for delivering messages but also as a strategy for shaping children’s character in accordance with Islamic values. Future researchers are encouraged to broaden the focus to include comparative studies of Islamic digital communication models, family involvement, and the influence of emerging technologies—such as Islamic game-based learning applications or augmented reality—on the internalization of moral values in children.